Acting Out Our Vanities. Why are university theatre students acting in productions, and how are we assessing them? - Michael McCal; John Freeman (Antropologia e Teatro)
This article casts a critical eye over the assumed need for staff-directed productions on BA theatre programs, asking what point and rationale these productions might serve, and what tutors are looking for when students are assessed in this area of practice. From these foundations the article moves into a breakdown of skills and ability, prior learning and the kind of boutique borrowing that sees theatre programs at university increasingly adopting the vocabulary of conservatoires. More provocation than prescription, the article suggests that the vocational training values of conservatoires are being absorbed by a number of universities in ways that are skewed when it comes to intent and problematic when it comes to assessment.